Up–Down Reader: An Open Source Program for Efficiently Processing 50% von Frey Thresholds - Gonzalez-Cano, Rafael; Boivin, Bruno; Bullock, Daniel; Cornelissen, Laura; Andrews, Nick; Costigan, Michael (Frontiers in Pharmacology, 2018)
Most pathological pain conditions in patients and rodent pain models result in marked alterations in mechanosensation and the gold standard way to measure this is by use of von Frey fibers. These graded monofilaments are used to gauge the level of stimulus-evoked sensitivity present in the affected dermal region. One of the most popular methods used to determine von Frey thresholds is the up-down testing paradigm introduced by Dixon for patients in 1980 and by Chapman and colleagues for rodents in 1994. Although the up-down method is very accurate, leading to its widespread use, defining the 50% threshold from primary data is complex and requires a relatively time-consuming analysis step. We developed a computer program, the Up-Down Reader (UDReader), that can locate and recognize handwritten von Frey assessments from a scanned PDF document, and translate these measurements into 50% pain thresholds. Automating the process of obtaining the 50% threshold values negates the need for reference tables or Microsoft Excel formulas and eliminates the chance of a manual calculation error. Our simple and straightforward method is designed to save research time while improving data collection accuracy and is freely available at https://sourceforge.net/projects/updownreader/ or in supplementary files attached to this manuscript.